Pencegahan Dan Penanganan Kekerasan Seksual Melalui Edukasi Komunikasi Asertif Dan Literasi Digital Pada Remaja Di Kabupaten Tasikmalaya - Lati Sari Dewi; Siti Amirah Makarim (CV. SINAR HOWUHOWU, 2026)
Sexual violence has become a serious social issue affecting adolescents both in offline and digital environments. Limited understanding regarding forms of sexual violence, self-protection, and reporting mechanisms often causes victims to remain silent and vulnerable. This community service activity aimed to improve adolescents’ understanding and awareness regarding the prevention and handling of sexual violence through educational approaches, assertive communication training, and digital literacy strengthening. The activity was conducted through counseling, interactive discussions, simulations, and mentoring involving adolescents in Kabupaten Tasikmalaya. The results showed increased participant understanding regarding forms of sexual violence, the courage to communicate assertively, awareness of digital safety, and understanding of reporting and assistance procedures. Overall, this activity contributed positively to strengthening adolescents’ self-protection capacity and creating a safer social environment.